The Significance of Albumin Concentration and Some of Its Altered Forms in Iraqi Patients with Chronic Hepatitis B Virus - Alubaidy, Zahraa F.; Hassan, Hathama R. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The liver synthesizes albumin, a pivotal protein that accounts for approximately 60-65% of total plasma proteins. During ischemic attacks linked to oxidative stress, reactive oxygen species, and acidosis, albumin’s properties undergo alterations. This leads to the generation of ischemia-modified albumin, characterized by a diminished metal-binding capacity, particularly for transition metals like copper, nickel, and cobalt.Objectives: This study aimed to assess the significance of serum albumin and ischemia-modified albumin concentrations in Iraqi individuals with hepatitis B virusMethods: A case-control study, including 50 patients with hepatitis B recruited from a Gastroenterology hospital in the Medical City/ Baghdad/ Iraq, was conducted from January to February 2023. The patients' group included males and females, ages 18 to 77 years, with a mean value of 44 years. Meanwhile, the study group consisted of 50 sex-matched normal healthy individuals. Albumin concentration was determined in the serum samples using a Biosystems kit, and ischemia-modified albumin concentration was measured through the albumin cobalt binding test. The ischemia-modified albumin/ [albumin] ratio and ischemia-modified albumin index were then calculated.Results: lower serum albumin concentration was measured in the patients' group, while the mean value of ischemia-modified albumin concentration in the patients' group and healthy control were 0.466 ± 0.114 absorbance unit & 0.395 ± 0.070 absorbance unit, respectively, with a statistically significant increase (P < 0.001). The ischemia-modified albumin ratio in the hepatitis B patients and control groups was 0.172 ± 0.073 and 0.117 ± 0.050, respectively, showing a significant increase (P < 0.001). Additionally, the ischemia-modified albumin index in the patients and the control groups were 0.491 ± 0.167 & 0.390 ± 0.131, respectively, with a statically significant increase (p